1993
DOI: 10.1071/ea9930609
|View full text |Cite
|
Sign up to set email alerts
|

Response of wheat, triticale, barley, and canola to lime on four soil types in north-eastern Victoria

Abstract: Lime requirement curves based on relative yield and pH data for 4 soil types were derived to estimate the amount of lime required to reach maximum yield for wheat, triticale, barley, and canola. Simple equations expressing lime requirement as a function of soil pH accounted for >90% of the variation in applied lime on 3 soil types (red brown earth, red podsolic, podsolised red earth). When aluminium and manganese (0.01 mol CaCl2/L extracted) were included in these equations, either individually or together,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…Bailey et al [25] found similar results in the United Kingdom (UK). For some Australian soils [23], the initial soil pH, together with soil Al, was a useful predictor of field lime requirement.…”
Section: Measuring Lime Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bailey et al [25] found similar results in the United Kingdom (UK). For some Australian soils [23], the initial soil pH, together with soil Al, was a useful predictor of field lime requirement.…”
Section: Measuring Lime Requirementsmentioning
confidence: 99%
“…In New Zealand, Edmeades et al [22], having shown that the biological optimal pH for pasture is 5.8 to 6.0, used data from field trials to determine the amount of lime required to achieve pH 6.0-the field lime requirement, or to use Black's concept, the biological lime requirement. Slattery and Coventry [23] adopted a similar approach in Australia for a range of crops and soils, defining the lime requirement as the amount of lime to obtain 90% of maximum yield.…”
Section: Measuring Lime Requirementsmentioning
confidence: 99%
“…Liming of acid soils can increase soil pH and alleviate Al toxicity to plants and thus maintain a suitable pH for the growth of a variety of crops (Slattery and Coventry, 1993;Mullen et al, 2006;Lollato et al, 2013;Mamedov et al, 2016). To establish which acid soils need to be ameliorated for plant growth and the target status of soil acidity after amelioration, the parameters of critical soil pH and soil Al concentration must be determined, and methods to achieve this need to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…In these areas awareness exists (mostly among primary producers) that acidification is a major problem. Here liming is seen as an economic option, despite the high cost of lime and freight [36,98]. In the medium rainfall areas, there is only limited awareness of acidification as a form of land degradation.…”
Section: Requirement For Productivity Growthmentioning
confidence: 98%